Mechanisms of resiliency against depression following the Deepwater Horizon oil spill. (October 2019) - Kaufman, John A.; Goldman, Zachary E.; Sharpe, J. Danielle; Wolkin, Amy F.; Gribble, Matthew O.
Abstract: Prior studies of oil spills have reported adverse impacts on mental health, but have not examined some potentially important moderators. In this cross-sectional analysis of n = 38, 361 responses to the 2010–2011 Gulf States Population Survey, we assessed the association of direct oil contact with depression severity following the Deepwater Horizon oil spill, and modification by self-mastery, emotional support, and cleanup participation using Tobit regression models accounting for the complex survey design. Oil contact was associated with increased depression severity. Among respondents with oil contact, depression was more severe for those reporting lower self-mastery. However, respondents with oil contact had lower depression severity if they participated in cleanup efforts, compared to exposed individuals who did not participate. This potential protective effect was larger for respondents with lower self-mastery. Our results are consistent with the notion that participation in recovery efforts may reduce depressive symptoms following oil spills among impacted individuals. Highlights: Oil contact was associated with higher depression severity. For those with oil contact, those with low self-mastery had higher depression. Among the exposed, cleanup participants had lower depression than non-participants. Low self-mastery cleanup participants had lower depression than non-participants. Association of oil contact with depression not modified by emotional support level.